Poder e moda: vestindo-se bem, que mal tem?: a Mesbla Magazine e o consumo feminino capixaba, na cidade de Vitória ES, 1952 a 1972 - Ferreira, Louise Maestri (2019)
This dissertation deals with the fashionable consumption power of upper middle class capixaba and the historical development of Mesbla Magazine, the first large department store, object of this study, which established its economic and social power in the city of Vitoria, capital of Espírito Santo, located on Princesa Isabel Avenue, promoting new habits of behavior to the Vitorian society in 1952 to 1972. The objective of this work was to analyze the changes in the fashion consumption sense of women belonging to the upper middle class of the city. The time-cut of the research began in 1952, when the store was opened, and its important milestone was the 1960s, when the process of industrialization and modernization of the urban space of Vitória gained sharper outlines, due to the changes in the spheres of commerce, sociability and fashion consumption in the city. As a methodology, we used the monographic study of exploratory nature, a case study, based on discourse analysis based on interviews with people who attended the trade in the neighborhood Centro de Vitória before the arrival of Mesbla and after the arrival of the store, such as seamstresses, consumers, owners and store owners. In order to do this, we tried to demonstrate the importance of the triad: fashion consumption, department store and female behavior, in the construction of the urban space and in the lifestyle of the women of the city, analyzing the social development of the city center. Documentary research proved that, through normative discourses, the center of Vitória was established as a space of sociability and status quo. Moreover, on the arrival of the Mesbla Store, because it is a public space of this sociability, the sense of consumption, in cultural terms, is reinterpreted by women, in relation to the use of women's fashion and the use of goods to construct the archetype of consumers capixaba´s.